The Tale of Tom Kitten and Jemima Puddle-Duck - Potter, Beatrix (Frederick Warne & Co, 1993)
The Tale of Tom Kitten is set in the cottage garden Beatrix created herself at Hill Top, the farm she owned near the village of Sawrey. Tom and his sisters look so smart in their new clothes. When their mother sends them outside while she waits for her visitors, she couldn't possibly guess what kind of mess they are going to get themselves into! Searching for a convenient nesting-place, befuddled Jemima Puddle-Duck chooses a fox's den.
Keywords: Juvenile literature-Fiction